2014
DOI: 10.1007/s13593-014-0227-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved wheat grain yield by a new method of root selection

Abstract: International audienceWheat is a major source of protein for human food, a critical issue at a time when mankind is growing by 77 million people per year. Wheat was domesticated approximately 10,000 years ago and has been systematically bred for about 200 years. However, this breeding selection has been done using only aerial plant parts. Indeed, wheat roots, the hidden half of plant, were not considered in breeding programs due to the lack of an appropriate method. Here, we evaluated roots of 18 wheat populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
(41 reference statements)
2
42
0
3
Order By: Relevance
“…5). Several recent studies3637 confirmed that using root C as a breeding criterion was efficient. In addition, these authors succeeded in using root C to select for high grain yields in wheat and barley.…”
Section: Discussionmentioning
confidence: 89%
“…5). Several recent studies3637 confirmed that using root C as a breeding criterion was efficient. In addition, these authors succeeded in using root C to select for high grain yields in wheat and barley.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, ancient and wild wheat species can be utilized in breeding programs to improve superior genotypes with large and deep rooting as well as high yield. It was reported that the root system size was correlated with grain yield (Heřmanská et al, 2015). However, studies on root system of those genotypes are insufficient because root studies have difficulty to conduct and harvest.…”
Section: Introductionmentioning
confidence: 99%
“…The probability of the successful selection of a larger root system according to the electrical capacitance is high. In recent years, the size of the root system (measured by electrical capacitance) has been used as a criterion for the selection of genotypes that are tolerant to drought, such as those of spring barley (Chloupek et al, 2010;Svačina et al, 2014) and winter wheat (Heřmanská et al, 2015). It was verified that varieties of wheat and barley with a larger root system size provided higher yields and contained more assimilates (more starch in wheat and barley and more glycid extract in barley) and less nitrogenous substances than those varieties with a smaller root system.…”
Section: Methodological Developments Modifications and Criticisms Ofmentioning
confidence: 99%
“…A prospective in situ method with the potential to save money, labour and time is measuring the size of the root system by its electrical capacitance as a part of the electrical impedance. This unique method was originally published by Chloupek (1972) and has been intensively developed at the Mendel University in Brno, Czech Republic (Chloupek et al, 2010;Středa et al, 2012;Středa and Chloupek, 2013;Svačina et al, 2014;Heřmanská et al, 2015) in the last decade. The method is applicable under field conditions and allows the detection of fine structures in the root system.…”
Section: Methods Descriptionmentioning
confidence: 99%